Da tela de algodão às telas virtuais: o artista plástico e as possibilidades do digital - Brantes, Hélio Renato Silva (2014)
This Master dissertation developed in the Postgraduate Program in Art and Visual Culture at FAV / UFG , in Visual Poetics Research and Creative Processes line, part of an exploratory theoretical and practical research that aims to reveal the possibilities of working with artistic poetic having as a conductor bias the trajectory of the means of production an d creation of art and new technologies in the field of cyber art. It introduces the artistic trajectory of the researcher through the universe of painting on traditional support and the technical and technological paths followed by image makers throughout art history with emphasis on the rise of the so-called numerical art of digital basis. Conceptually, holds up in the struggle of man in the use of new technologies and in the approach of the concept of expanding the body through the machines, the "posthuman" body. Simultaneously to the theoretical research, the work involved the development of experimental poetics through a creation exercise that incorporates to the artwork of painting on cotton canvas the unfolding in a digital visual narrative.